Odorant receptor co-receptors affect expression of tuning receptors in Drosophila - Long, Teng; Mohapatra, Pratyajit; Ballou, Sydney; Menuz, Karen (Frontiers in Cellular Neuroscience, 2024)
Insects detect odorants using two large families of heteromeric receptors, the Odorant Receptors (ORs) and Ionotropic Receptors (IRs). Most OR and IR genes encode odorant-binding "tuning" subunits, whereas four (Orco, Ir8a, Ir25a, and Ir76b) encode co-receptor subunits required for receptor function. Olfactory neurons are thought to degenerate in the absence of Orco in ants and bees, and limited data suggest this may happen to some olfactory neurons in Drosophila fruit flies as well. Here, we thoroughly examined the role of co-receptors on olfactory neuron survival in Drosophila. Leveraging knowledge that olfactory neuron classes are defined by the expression of different tuning receptors, we used tuning receptor expression in antennal transcriptomes as a proxy for the survival of distinct olfactory neuron classes. Consistent with olfactory neuron degeneration, expression of many OR-family tuning receptors is decreased in Orco mutants relative to controls, and transcript loss is progressive with age. The effects of Orco are highly receptor-dependent, with expression of some receptor transcripts nearly eliminated and others unaffected. Surprisingly, further studies revealed that olfactory neuron classes with reduced tuning receptor expression generally survive in Orco mutant flies. Furthermore, there is little apoptosis or neuronal loss in the antenna of these flies. We went on to investigate the effects of IR family co-receptor mutants using similar approaches and found that expression of IR tuning receptors is decreased in the absence of Ir8a and Ir25a, but not Ir76b. As in Orco mutants, Ir8a-dependent olfactory neurons mostly endure despite near-absent expression of associated tuning receptors.Finally, we used differential expression analysis to identify other antennal genes whose expression is changed in IR and OR co-receptor mutants. Taken together, our data indicate that odorant coreceptors are necessary for maintaining expression of many tuning receptors at the mRNA level.Further, most Drosophila olfactory neurons persist in OR and IR co-receptor mutants, suggesting that the impact of co-receptors on neuronal survival may vary across insect species.